Feeding Strategies of Mangrove Leaf-Eating Crabs for Meeting Their Nitrogen Needs on a Low-Nutrient Diet - Gao, Xueqin; Lee, Shing Yip (Frontiers in Marine Science, 2022)
Sesarmid crabs play an important role in mangrove biogeochemical processes due to their leaf-eating and burrowing activities. How leaf-eating mangrove crabs meet their nitrogen (N) needs remains a puzzle, as N-poor leaf litter (<1% dry weight) cannot support the growth of most macrofauna. Several strategies for overcoming this challenge have been proposed, but the actual mechanisms remain unknown. We identified two categories of leaf-eating crabs according to their feeding habits (1): species active outside their burrows during low tide - we hypothesize that they meet their N needs through consuming the microphytobenthos (MPB) (hypothesis H1); and (2) species spending most of their time inside burrows - we hypothesize that they meet their N needs through N-fixation by associated microbes (H2). To test H1, we conducted a series of feeding experiments on the sesarmid crab Parasesarma affine (model species for category 1) with 13C- and 15N-enriched MPB and mangrove leaves. P. affine relied mainly on mangrove leaves as their C source and MPB as their N source, supporting H1. Two feeding experiments on Neosarmatium smithi (model species for category 2) showed that N limitation could be ameliorated by selecting seasonally available higher-quality food items such as floral parts, or by supplements from the associated nitrogen-fixing bacteria, as identified by genomic analysis. The strategy by which leaf-eating crabs meet their N needs may make significant contribution both to the growth of crabs and to their ecosystem functions of regulating the cycling of significant nutrient elements. The stoichiometric regulations by leaf-eating crabs to meet their N needs, such as food selection, can enhance trophic efficiency and nutrient transfer rate at the community level and ultimately increase nutrient turnover rate at the ecosystem level.